2021
DOI: 10.1021/acs.joc.1c00669
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Oxyacyloxylation of Propiolic Acids: Construction of Alkynyl-Containing α-Acyloxy Ketones

Abstract: Novel decarboxylative oxyacyloxylation of propiolic acids has been developed. This reaction provides an efficient access to alkynyl-containing α-acyloxy ketones from readily available starting materials and exhibits significant functional group tolerance. Furthermore, oxyacyloxylation of terminal alkynes and aliphatic propiolic acids was also developed. A possible reaction mechanism is proposed based on mechanistic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…To improve the yield of the decarboxylative acetoxylation, H 2 O utilization was tested and a slightly increased yield of 83% was observed when 2.5 equivalents of H 2 O was included (Table 1, entries [15][16][17]. Subsequently, the study was extended to testing the AcOH volume.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To improve the yield of the decarboxylative acetoxylation, H 2 O utilization was tested and a slightly increased yield of 83% was observed when 2.5 equivalents of H 2 O was included (Table 1, entries [15][16][17]. Subsequently, the study was extended to testing the AcOH volume.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we selected phenylpropiolic acid 1a as the model substrate for reaction uncovering and treated with 3.0 equivalents of PhI(OAc) 2 , 2.0 equivalents of H 2 O and 1 milliliter of acetic acid in acetone at 80 °C for 3 h. Surprisingly, the desired 2-oxo-2-phenylethyl acetate 2a was obtained in 48% yield, along with alkynyl-containing α-acyloxy ketone 3a as a byproduct, which was the main product in the work by Chen 16 (Table 1, entry 1). Through investigations of other hypervalent iodine reagents such as bis(trifluoroacetoxy)iodobenzene (PIFA), PhIO and 1-hydroxy-1,2-benziodoxol-3(1 H )-one (ABX), we found that PhI(OAc) 2 (DIB) gave the best yield of 94% (see ESI†).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we planned the synthesis of a set of bis- The keen interest of synthetic organic chemists towards α-acyloxy ketones is demonstrated by the numerous methods developed to obtain these substances (see for example Refs. [20][21][22][23][24]). However, the synthesis and the chemistry of bis-α-acyloxy diketones such as 2 (Scheme 1) are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%